Arsenic content in Portland cement: A literature review - Tenorio de Franca Talita; da Silva Raphaela; Sedycias de Queiroz Michellini; Aguiar Carlos (Wolters Kluwer Medknow Publications, 2010)
Portland cement (PC) is a hydraulic binding material widely used in the building industry. The main interest in its use in dentistry is focused on a possible alternative to mineral trioxide aggregate (MTA) because PC is less expensive and is widely available. In dentistry, PC has been used in dental procedures such as pulpotomy, pulp capping, repair of root perforation and root-end filling. The purpose of this article is review the dental literature about the PC, its composition with special attention to arsenic content, properties, and application in dentistry. A bibliographic research was performed in Bireme, PubMed, LILACS and Scopus data bases looking for national and international studies about the PC composition, properties and clinical use. It was observed that PC has favorable biological properties very similar to those of MTA. The PC has shown good cell proliferation induction with formation of a monolayer cell, satisfactory inflammatory response, inhibitory effect of prostaglandin and antimicrobial effect. Studies have shown that PC is not cytotoxic, stimulates the apposition of reparative dentin and permits cellular attachment and growth. Regarding arsenic presence, its levels and release are low. PC has physical, chemical and biological properties similar to MTA. Arsenic levels and release are low, therefore, unable to cause toxic effects.